Seven key state constituencies of Terengganu’s politics (1999-2018) - Ilyas Abdullah,; Muhammad Syakir Idris, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Since the 1959’s first general election, UMNO-BN was the only political party that dominated the federal government and in almost every state. Predicting the winners were a clear-cut and straight forward feat. This study analysed the variable voting patterns in the last five state elections of Terengganu in 1999, 2004, 2008, 2013 and 2018. This study used qualitative data collection methods through secondary sources. The data is obtained through materials such as books, articles, theses, journals, internet and others which studied the intense rivalry between two major Malay Muslim based political parties of UMNO-BN and PAS. Based on the result of the 10th GE, both parties have enjoyed equal chances of winning the state election. The election results of the state from 1999 to 2018 also indicated that any political party that won the state’s key seven constituencies would most likely form the state government as well, on top of it winning own strongholds nonetheless. In the 2018 election PAS managed to increase the number of seats it won when it took control of all eight of its strongholds while also retaining victory in all seven key state constituencies. In addition, PAS also managed to seize seven UMNO-BN strongholds, namely Kota Putera, Jabi, Pengkalan Berangan, Ajil, Kemasik and Air Putih. In conclusion, this study is important to predict the outcome of the next general election in Terengganu.